HUBUNGAN FAKTOR INDIVIDU DAN PEKERJAAN DENGAN PERILAKU TIDAK AMAN PADA PEKERJA KONSTRUKSI Y TAHUN 2023 - Wienata, Kethlin; Duana, I Made Kerta (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025, 2025)
ABSTRACT Unsafe actions cause 88% of workplace accidents, with 10% due to hazardous conditions and 2% to other factors. Individual and job-related factors are the primary causes of unsafe actions. This study aims to explore the link between these factors and unsafe actions among workers at the 2023 Y construction project. This research employs a quantitative research design with an analytical method and a cross-sectional approach conducted at the Y Construction Project. Data were obtained through questionnaires and observations. The sampling technique employed was purposive sampling among construction project workers. The data utilized were primary data based on the questionnaires. The study found that 43.2% of workers exhibited unsafe behavior. Work experience (p=0.005), knowledge (p=0.002), attitude (p=0.018), work duration (p=0.040), job type (p=0.001), and use of personal protective equipment (PPE) (p=0.005) were identified as variables linked to unsafe behavior through bivariate analysis. Multivariate analysis using logistic regression highlighted that work duration had the greatest impact on unsafe behavior (OR=9.34; CI=1.42-61.29; p=0.02). Addressing unsafe behavior can involve providing occupational health and safety (OHS) education, emphasizing PPE usage, and enhancing worker awareness of the importance of working safely for their own well-being. Keywords: Unsafe Behavior, Construction Workers, Construction Projects